Survival motor neuron protein and neurite degeneration are regulated by Gemin3 in spinal muscular atrophy motoneurons - Miralles, Maria P.; Sansa, Alba; Beltran, Maria; Soler, Rosa M.; Garcera, Ana (Frontiers in Cellular Neuroscience, 2022)
Spinal Muscular Atrophy (SMA) is a genetic neuromuscular disorder caused by reduction of the ubiquitously expressed protein Survival Motor Neuron (SMN). Low levels of SMN impact on spinal cord motoneurons (MNs) causing their degeneration and progressive muscle weakness and atrophy. To study the molecular mechanisms leading to cell loss in SMN-reduced MNs, we analyzed the NF-κB intracellular pathway in SMA models. NF-κB pathway activation is required for survival and regulates SMN levels in cultured MNs. Here we describe that NF-κB members, IKKβ and RelA, were reduced in SMA mouse and human MNs. In addition, we observed that Gemin3 protein level was decreased in SMA MNs, but not in non-neuronal SMA cells. Gemin3 is a core member of the SMN complex responsible for small nuclear ribonucleoprotein biogenesis, and it regulates NF-κB activation through the mitogen-activated protein kinase TAK1. Our experiments showed that Gemin3 knockdown reduced SMN, IKKβ, and RelA protein levels, and caused significant neurite degeneration. Overexpression of SMN increased Gemin3 protein in SMA MNs, but did not prevent neurite degeneration. These data indicated that Gemin3 reduction may contribute to cell degeneration in SMA MNs.